PERBANDINGAN PEMERIKSAAN WIDAL DAN SALMONELLA IgG/ IgM PADA PASIEN SUSPEK DEMAM TIFOID - Nurhidayanti; Denny Juraijin; Rafli Wilendra (IKesT Muhammadiyah Palembang, 2023)
Introduction: Typhoid fever is still a very important health problem. This disease is still often found in developing countries located in tropical areas such as Indonesia and subtropical areas. Acute typhoid fever is an acute systemic infectious disease caused by the microorganism Salmonella enteric serotype typhi known as Salmonella typhi (S. typhi). Laboratory examinations to establish the diagnosis of typhoid fever in general can be checked with the Widal test and Salmonella IgG/IgM, tubex test and culture test. Several diagnostic methods are faster, easier to perform and affordable for developing countries with fairly good sensitivity and specificity, such as Widal and salmonella IgG/IgM tests, starting to be used in Indonesia. Purpose: This study was to determine the examination of Widal and salmonella IgG/IgM in patients with suspected typhoid fever.. Research Method: The type of research used was cross sectional, this research was conducted in the Laboratory of Bunda Palembang Hospital. Samples were serum/plasma of patients with suspected typhoid fever. Results: The results showed that there were 11 patients with suspected typhoid fever who were Widal positive and then confirmed using salmonella IgG/IgM and 6 samples were diagnosed positive with typhoid fever. Data analysis using chi-square test obtained p value = 0.014. Conclusion: The conclusion of this study is that there are significant differences in the examination of Widal and salmonella IgG/IgM in patients with suspected typhoid fever